Evaluation of Justicia gendarussa crude leaf extract for enhancement of flavonoids production via adventitious root culture and genetic modifications - Ayob, Zahidah (2017)
Justicia gendarussa extract possesses various bioactivities associated with the availability of flavonoids. Low availability of flavonoids could limit or even hinder the bioactivities effects. Therefore, attempts to enhance the flavonoids production via tissue culture approaches are being studied. This study aimed to optimize flavonoids contents in J. gendarussa using different tissue culture systems (in vitro plant regeneration and adventitious root culture) and genetic transformation methods. The cytotoxicity of plant extracts against various cancer cell lines was also evaluated. Detection and quantification of naringenin and kaempferol were performed using GC-FID. Cytotoxicity tests of crude extract against cancer cell lines (MCF-7, MDA-MB-231, MDA-MB-468, HT-29, HeLa and BxPC-3) were determined by MTT assay. The optimization of elicitors used including yeast extracts (YE), casein hydrolysate (CH) and proline (P) at various concentrations (0, 0.2, 0.4, 0.6, 0.8 or 1.0 mg/L) were examined using nodal explants from in vitro plants. Adventitious roots were inoculated into MS liquid medium supplemented with IBA (2.0-4.0 mg/L). For genetic transformation studies, plasmids pCAMBIA 1305.2, which harbour the PKS gene and plant selectable marker, HPT for hygromycin resistance was used to transform nodal explants of J. gendarussa under the optimized transformation protocol using biolistic and Agrobacterium tumefaciens-mediated transformation. Results showed that mature leaves extract, JG1 had the highest naringenin (444.35 ± 81.43 mg/kg) and kaempferol (1591.80 ± 94.91 mg/kg), while the cytotoxicity against BxPC-3 cell was the strongest (IC50~16 μg/mL). The highest naringenin and kaempferol contents were obtained in leaf crude extracts when treated with 0.6 g/L of CH (1180.30 ± 50.23 mg/kg) and 0.6 g/L of P (385.01 ± 13.10 mg/kg), respectively. Adventitious root culture produced high naringenin (97.54 ± 5.47 mg/kg) and kaempferol (853.82 ± 56.52 mg/kg) when treated with 2.0 mg/L IBA. The optimal parameters for biolistic method were established at 1100 psi helium pressure and 12 cm target distance with 95% of transformation efficiency. Meanwhile, the optimal transformation condition of A. tumefaciens method was bacterial concentration at OD600nm ~ 0.8, 20 minutes of inoculation time, 500 μM AS and 1 cm explant size with 90% transformation efficiency. Even though A. tumefaciens method produced lower percentage of transient GUS expression than biolistic method, a few transformed explants were successfully produced. The integration of the PKS gene with band size of 1200 bp into the genome of transgenic plants were verified by PCR, sequencing and subsequently confirmed by Southern blot analysis. The content of kaempferol were found to be higher in stem extracts of transgenic plants (450.40 ± 7.82 mg/kg) than non-transgenic plants (197.13 ± 2.29 mg/kg). In conclusion, addition of elicitors, establishment of adventitious root culture and A. tumefaciens-mediated transformation could enhance flavonoid contents in J. gendarussa.